Biceps Femoris long head Architecture and Passive Tissue Stiffness and Their Relations to Performance Variables - Laatikainen-Raussi, Iida (2024)
The purpose of this master’s thesis was to investigate the reliability of ultrasound elastography (SWE) imaging in passive muscles, changes in the shear modulus (“stiffness”) along the biceps femoris long head (BFlh) muscle length, the architecture of the BFlh (muscle thickness (MT), fascicle length (FL) and pennation angle (PA)) and the relations of these muscle characteristics with performance variables (30 m speed, counter movement jump (CMJ), static jump, Nordic hamstring exercise, isokinetic hamstring:quadriceps-ratio). Hamstring injuries are common and cause a lot of absences, especially in sports involving high-intensity running. The hamstring muscles play a significant role in human movement, as they extend hip, flex knee, and participate in rotating the knee joint. BFlh, which is located laterally on the posterior thigh, is the most often injured hamstring muscle. Ultrasound elastography (SWE) is a relatively new technology to evaluate tissue stiffness. The technique is based on the detection of shear waves; the propagation is faster the stiffer the medium. The validity and reliability of SWE in muscle and tendon imaging has been studied, but re-porting varies. Mainly, it has been found to be a valid and reliable method, but it has its own limitations. All ultrasound measurements in this study were performed in one measurement session at rest. Participants of the study were female football (soccer) players (N=29). The reliabilities of the ultrasound measurements (SWE and architectural measurements) were good to excellent (ICC for SWE 0.854, p=0.000; PA 0.935, p=0.000; FL 0.963, p=0.000 and MT 0.982, p=0.000). There were statistically significant differences in shear modulus along the BFlh in the right but not in the left leg. No high correlations were found between muscle architecture, shear modulus and performance variables. Some statistically significant moderate and low correlations were found, as relevant ones shear modulus and 30 meters sprint time (0.450, p < 0.05), fascicle length and jump performance (CMJ 0.379, static jump 0.441, p < 0.05). The SWE measurements within the measurement session proved to be reliable, but the SWE measurement technology and analysis methods contain their own weaknesses. In the future, SWE may be a useful tool when monitoring muscle injury prevention and rehabilitation programs. Reliable comparisons between ultrasound measurements and performance variables re-quire more precisely scheduled measurements and additional measurement methods (such as EMG) to support the findings. Imaging shear modulus closer to the muscle-tendon junctions could show greater intra-muscular differences in SWE measurements.